An Electrochemical Sensor for Ultrasensitive Determination the Polychlorinated Biphenyls. (10th March 2016) - Zheng, Xiangli; Li, Hongli; Xia, Fangquan; Tian, Dong; Hua, Xiaoxia; Qiao, Xueying; Zhou, Changli
Graphical abstract: Highlights: A new simple and ultrasensitive sensing platform by using β-cyclodextrin polymer/rGO/polypyrrole modified pyrolytic graphite electrode (β-CDP/rGO/PPy/PGE) was constructed. The proposed electrochemical sensor exhibited high sensitivity for the determination polychlorinated biphenyls (PCBs) which have no electrochemical activity. The newly developed method was successfully applied to quantitative determination of PCBs level in sediment core collected from Lake Nansihu. Abstract: A new electrochemical sensor for ultrasensitive determination the polychlorinated biphenyls (PCBs) is presented here, exploiting the electrochemical route of sensing which has a distinct advantage over other conventional analysis. Chemically converted reduced graphene oxide modified with β-cyclodextrin polymer (β-CDP), being more soluble in water and the formation constants of target molecules with β-CDP are generally stronger and larger than that of β-CD, provides a platform for the electrochemical detection of PCBs using ferrocene as redox indicator. Ferrocene can form a host-guest complex with β-CDP. PCBs will replace the ferrocene in the cavity due to its higher affinity towards β-CDP, offering wide linear range and higher detection sensitivity via selective host-guest interaction. As ferrocene is a well known redox probe and hence can be easily detected using differential pulse voltammetery (DPV) technique. The new method exhibited excellent analytical performance toward PCBs with a low detection limit of 5.0 × 10 −13 M (S/N = 3). More importantly, the developed method was applied to the quantitative determination of PCBs level in sediment core collected from Lake Nansihu and displayed satisfactory results. These results indicate that the method offers considerable potential for trace PCBs monitoring. We believe that the method has a profound impact on the design of a convenient platform for rapid screening and determination of PCBs in environment.